Keragaman Genetik Ikan Tongkol Abu-Abu (Thunnus tonggol) yang Didaratkan di Pasar Ikan Sagulung, Batam, Kepulauan Riau Berdasarkan DNA Mitokondria - Suryany Devy; Ida Ayu Astarini; I Nyoman Giri Putra; Andrianus Sembiring; Luh Astria Yusmalinda; M. Danie Al Malik; Ni Putu Dian Pertiwi (Journal of Marine and Aquatic Sciences, 2021)
Longtail Tuna (Thunnus tonggol) is one of the neritic species of tuna from the Scrombridae family. T. tonggol is oceanicromus and ussually found in tropical and subtropical waters in the Indo-Pacific region. Although known as one of the tuna species, the information of this species is very lacking, especially in Indonesia. Therefore, this study aims to determine the genetic diversity and kinship relationships of longtail tuna (T. tonggol) collected at Sagulung fish market, Batam, Riau Islands. Molecular analysis were carried out using genetic markers namely mitochondrial D-loop (control regian) with the stages of DNA extraction, PCR (Polymerase Chain Reaction), electrophoresis, sequencing, and data analysis. A total of 21 longtail tuna samples were identified using molecularly and confirmed as T. tonggol species, which have a base length ranging from 482 - 523 bp (base pairs). The value of haplotype diversity (Hd) of longtail tuna was 1,00000 and the value of nucleotide diversity (?) was 0,01654. The results of phylogenetic tree reconstruction showed that all samples collected were in the same group (clade) with the average genetic distance in one T. tonggol clade obtained a value of 0.010 which has a close relationship between samples. This result can be use as additional information for longtail tuna species in Indonesia.